2013
DOI: 10.5694/mja13.10621
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in children

Abstract: for those relating to issues discussed recently (within six weeks) in the BMJ. * We do not routinely acknowledge letters. Please send a stamped addressed envelope ifyou would like an acknowledgment. * Because we receive many more letters than we can publish we may shorten those we do print, particularly when we receive several on the same subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 52 publications
(98 reference statements)
2
40
0
3
Order By: Relevance
“…1 Gangguan ini merupakan masalah yang umum terjadi pada anak dan remaja dengan prevalensi antara 25%-40%. 2,3 Pada anak usia sekolah, prevalensi gangguan tidur mencapai 30%. 4 Anak dengan gangguan tidur yang kronis dapat mengalami gangguan belajar dan memori di sekolah, iritabel, perubahan mood, kesulitan mempertahankan perhatian, dan perubahan perilaku seperti agresif, hiperaktif, atau impulsivitas.…”
unclassified
See 1 more Smart Citation
“…1 Gangguan ini merupakan masalah yang umum terjadi pada anak dan remaja dengan prevalensi antara 25%-40%. 2,3 Pada anak usia sekolah, prevalensi gangguan tidur mencapai 30%. 4 Anak dengan gangguan tidur yang kronis dapat mengalami gangguan belajar dan memori di sekolah, iritabel, perubahan mood, kesulitan mempertahankan perhatian, dan perubahan perilaku seperti agresif, hiperaktif, atau impulsivitas.…”
unclassified
“…4 Anak dengan gangguan tidur yang kronis dapat mengalami gangguan belajar dan memori di sekolah, iritabel, perubahan mood, kesulitan mempertahankan perhatian, dan perubahan perilaku seperti agresif, hiperaktif, atau impulsivitas. [1][2][3][4] Gangguan tidur pada anak dan remaja ditunjukkan dengan jumlah waktu tidur yang tidak adekuat disebabkan oleh kombinasi faktor intrinsik dan ekstrinsik. Faktor intrinsik di antaranya perubahan perkembangan alami, seperti pergeseran irama sirkadian selama pubertas, delayed sleep phase syndrome, dan sleep disordered breathing (SDB), seperti obstructive sleep apnea (OSA).…”
unclassified
“…Many sleep problems past infancy often are not discussed by parents with children's pediatricians, which leads to many sleep disturbances going undetected and untreated (Waters, Suresh, & Nixon, 2013;Mindell & Owens, 2003). It has also been well documented that many sleep problems in infants and young children tend to persist over time without treatment, highlighting the importance of timely treatment (Lam, Hiscock, & Wake, 2003;Mindell et al, 2006;Owens, 2008).…”
mentioning
confidence: 99%
“…In a 4 year follow-up study of Finnish children, Simola, Liukkonen, Pitkaranta, Pirinen, & Aronen (2012) found that children with sleep problems that continued from preschool to the school aged years had a 16-fold increase risk in attention problems, social problems, aggression, somatic complaints, and anxious/depressed moods. Thus, appropriate, early screening and assessment of sleep and identification of possible sleep disturbances in treatment settings is vital (Waters et al, 2013). Improved understanding of possible contributing factors such as other presenting problems and use of electronics and television that may impact sleep is also needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation